KARAKTERISASI ELEKTROLIT POLIMER OPTIMUM KITOSAN/PVA+KOH - R.Putri -; A.Maddu -; Irzaman - (Sistem Informasi, 2011)
The blend-based polymer electrolyte comprising of chitosan and polyvinyl alcohol (PVA) as host polymers and potassium hydroxide (KOH) 35% wt as the complexing salt was studied. Polymer electrolyte were obtained by the casting technique. FTIR, XRD, SEM and EDX studies have been made to investigate the structural, complexation in film morphology of the polymer electrolyte.